Alkaline magmatism in the Paraná Basin: A comparative study. I. Geology, petrography and mineralogy - Gomes, Celso de Barros (Geochimica Brasiliensis, 2025)
Over two hundred occurrences of alkaline rocks are known in different areas of Brazil, Paraguay, Bolivia and Uruguay territories. They are grouped into 16 alkaline provinces that present variable extent, composition and age and are mainly concentrated along the borders of Paraná, Bauru and Santos sedimentary basins. The geological setting for all the occurrences is discussed, with the prevailing emplacement represented by. crustal discontinuities, such as arches, rifts, lineaments, and faults. Most of these structural features correspond to old fractures that were reactivated in the Mesozoic during the Wealdenian episode. For a better characterization and correlation of the numerous occurrences, the alkaline rocks are arranged into diverse associations and compared their principal geological, petrographic and mineralogical aspects.